Gold exchange analysis: testing the market efficiency by using statistical method an application with daily Turkish gold return - Çinko, Murat (My University, 2000)
The main aim of this thesis is to test the existence of nonlinearties in daily gold return in Turkey. Since the market efficiency theory says that prices are follows random walk, if it can be shown that gold return has a nonlinear dependence and chaos the hypothesis is refuted. There are five nonlinearity tests that are common in the literature. These are namely: BDS test, Hinich Bispectral test, White Neural Network test, NEGM Liapunov test, and Kaplan test. In this study the data between 01.08.1995 and 31.05.2000, with 1193 data point, is used and the. BDS, Kaplan, and White tests detect nonlinearity in the data where Hinich Bispectral, and NEGM Liapunov exponent tests reject the third order nonlinearity and chaos, respectively. As a conclusion we have found nonlinearity in gold returns, however neither chaos nor third order nonlinerity could be found.

Bu tezin temel amacı günlük altın getirisinin doğrusal olmayan veya kaotik bir yapısının olup olmadığını test etmektir. Bu tezde beş tane test yapılmıştır: BDS test, Hinich bispectrum test, White sinir ağları testi, NEGM Liapunov üssü testi, Kaplan testi. Bu çalışmada kullanılan veriler 1 Ağustos 1995 ve 31 Mayıs 2000 tarihleri arasındaki toplam 1193 veriyi kapsar. Bu testler sonucunda bulunanlar ise BDS, White, Kaplan testlerinde doğrusal olmayan bir yapının var olduğu kabul edilmiş. Binich bispectrum testinde ise üçüncü dereceden doğrusal olmayan bir ilişki reddedilmiş. Son olarak NEGM Liapunov üssü testinde ise kaos reddedilmiş.
Keywords: Menkul kıymetler-Altın; Yatırımlar-Altın